Secretion of Proinflammatory Cytokines and Chemokines during Amphotericin B Exposure Is Mediated by Coactivation of Toll-Like Receptors 1 and 2 - Razonable, Raymund R. (American Society for Microbiology, 2005)
Amphotericin B (AmB) is a ligand of toll-like receptor 2 (TLR2). Here, we demonstrate the participation of TLR1 in AmB-induced cell activation that led to the secretion of tumor necrosis factor alpha, interleukin 6 (IL-6), and IL-8. Hence, TLR2-TLR1 coactivation serves as the underlying mechanism for the proinflammatory toxicities associated with AmB.